Genomic identification, evolutionary analysis, and transcript profiling of protein phosphatase 2C in Solanum lycopersicum - Miah Mohammad Sakib; Md. Sifatul Islam; Asifur Rob Bhuya; Md. Rihan Kabir Shuvo; Mohammad Abdullah-Al-Shoeb; Muhammad Abul Kalam Azad; Ajit Ghosh (Scientific Reports)
Abstract Protein phosphatases (PPs) are a class of enzymes that play a critical role in cellular regulation by catalyzing the removal of phosphate groups from proteins. This dephosphorylation process is essential for controlling and modulating various cellular functions, including signal transduction, cell cycle progression, metabolic regulation, and stress responses. This study focuses on the comprehensive genomic identification, evolutionary analysis, and transcript profiling of the PP2C gene family within Solanum lycopersicum, an economically significant crop with substantial agricultural and nutritional importance. A total of 95 PP2C members have been identified in tomato, which was divided into 12 subgroups. An evolutionary comparison of the tomato PP2C members with other plant species demonstrated that they shared a common ancestor. A total of 14 SlPP2Cs have arisen from segmental duplication events, while no tandem duplication was detected. Certain SlPP2C genes exhibited unique expression patterns in specific tissues, with only a limited number of SlPP2C genes being expressed in all tissues, while almost all SlPP2Cs are upregulated during the flowering stage. Gene expression analysis revealed elevated transcript levels of SlPP2C22, SlPP2C30, and SlPP2C52 during drought stress. An increase in total PP2C enzyme activity was also observed which indicates their significance in drought stress. These findings add to the comprehension of the evolutionary history and significance of tomato PP2C in managing abiotic stress and pave the way for additional verification of the functional aspect of these PP2C genes in tomato.